IDDQ Testing of Low Voltage CMOS Operational Transconductance Amplifier - Maninder Kaur; Jasdeep Kaur (International Journal of Electrical and Computer Engineering (IJECE), 2018)
The paper describes the design for testability (DFT) of low voltage two stage operational transconductance amplifiers based on quiescent power supply current (IDDQ) testing. IDDQ testing refers to the integral circuit testing method based upon measurement of steady state power supply current for testing both digital as well as analog VLSI circuit. A built in current sensor, which introduces insignificant performance degradation of the circuit-under-test, has been proposed to monitor the power supply quiescent current changes in the circuit under test. Moreover, the BICS requires neither an external voltage reference nor a current source and able to detect, identify and localize the circuit faults. Hence the BICS requires less area and is more efficient than the conventional current sensors. The testability has also been enhanced in the testing procedure using a simple fault-injection technique. Both bridging and open faults have been analyzed in proposed work by using n-well 0.18µm CMOS technology.